Formation of Aldehydes by Direct Oxidative Degradation of Amino Acids via Hydroxyl and Ethoxy Radical Attack in Buffered Model Solutions - Wietstock, Philip C.; Methner, Frank-Jürgen (BrewingScience, 2013)
The formation of aldehydes in bottled beer is promoted by the presence of oxygen and transition metal ions. In this paper, a so far unrevealed pathway to explain this phenomenon is presented. Leucine, isoleucine, and phenylalanine were oxidized by H2O2-Fe2+ in ?beer-like? buffered model solutions?(pH 4.5; 5?%?(v/v) ethanol) at room temperature thereby yielding 3-methylbutanal, 2-methylbutanal, phenylacetaldehyde, and benzaldehyde, respectively, as measured and identified by solvent extraction and HRGC-MS. Further trials revealed that the aldehydes formed were significantly correlated with radical concentration as determined by electron spin resonance (ESR) spectroscopy indicating that hydroxyl radicals (?OH) and ethoxy radicals (EtO?) are involved in the pathway. A reaction route for ?beer-like? model systems is featured and confirmed by a storage trial in which a steady increase of aldehydes over a time span of 18 days could be demonstrated.